A pilot study on the Vietnamese labour market and its social and economic context - Uwe Blien; Phan thi Hong van (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
This paper presents a regional case study of the labour market and its surrounding of Vinh City in central Vietnam, based on surveys conducted in 1999 and 2005. By including the time dimension and surveying samples with over 6000 individuals respectively it is possible to identify precisely the changes that have taken place within six years. The results reflect an enormous development process. Incomes increased fast and many structural parameters of the economy adapted to the new institutional setting of a market economy. The absolute level of income and of the standard of living is still low, however. A key finding of the analyses is that vocational training is meeting with large demand in private enterprises and is therefore of considerable importance for Vietnam's development process. Another important finding is that educational investments pay more in private enterprises.
Keywords: J31; J42; J65; 330; Arbeitsmarktentwicklung; ökonomische Faktoren; soziale Faktoren; Einkommensentwicklung; Wirtschaftsstrukturwandel; Marktwirtschaft; Berufsausbildung; Bildungsinvestitionen; Bildungsertrag; Lebensstandard; regionaler Arbeitsmarkt; Stadt; Arbeitslosenquote; strukturelle Arbeitslosigkeit; Arbeitsmarktpolitik; Arbeitslosenversicherung; Armut; Privatwirtschaft; Vietnam